Recommendations to improve physical activity prescription for the cystic fibrosis population: an Irish perspective - Nicola Hurley; Bróna Kehoe; Noel McCaffrey; Karen Redmond; Lydia Cullen; Niall M. Moyna (BMC, 2020)
Abstract Background Physical activity (PA) is a well-established therapeutic modality for the maintenance and improvement of long-term health in cystic fibrosis (CF). Healthcare professionals (HCP) are considered credible and well-placed messengers for the delivery of PA advice. Limited research exists investigating the extent of PA prescription within CF care. This study aimed to identify Irish HCP i) knowledge and practice of, and ii) motivators and barriers to PA prescription, and iii) proposed strategies to optimize PA promotion and prescription in CF populations. Methods HCP from six designated CF centres in Ireland and members of the national physiotherapy CF clinical interest group were invited to participate. Following an expression of interest, each HCP (n = 81) received an email containing the plain language statement and link to the online survey. 48 HCP (physiotherapists n = 24, other n = 24) completed the 30-item investigator-developed survey, which included multiple choice single answer, matrix style and open-ended questions. Results Most HCP (81%) acknowledged that discussing PA with CF patients was part of their professional role. Almost all physiotherapists (95%) reported having sufficient knowledge regarding PA prescription, compared to 17% of other HCP. All physiotherapists reported discussing PA at every patient interaction, with 81% employing the current consensus guidelines, compared to 33 and 5% of other HCP, respectively. Among the most common barriers reported by HCP to recommending PA to their CF patients were; lack of motivation and compliance among patients to adhere to PA advice, limited availability of PA programmes to refer their patients to, limited time with patients during clinic visits and a lack of knowledge regarding PA prescription for CF care. Three-quarters of HCP reported a need to improve PA services for CF patients in Ireland. Conclusion As people with CF are living longer, it is imperative that HCP are expanding their scope of practice to include discussions around PA at every patient visit. Formal educational opportunities in the form of continuing professional development programmes are warranted for CF HCP to optimize long-term patient management and outcomes. There is also a need to develop patient-centered and evidence-based PA programmes underpinned by theories of behaviour change to enhance motivation and compliance among CF patients.